Potencialidade ornamental de glandularia peruviana (L.) small cultivada a partir de diferentes formas de programação e substratos - Dall'Agnese, Luciana (2015)
Currently, it is necessary to reduce costs and enviromental contamination in order to encourage the organic floriculture and sustainable landscaping. Glandularia peruviana (L.) Small, the peruvian verbena, is a herbaceous species and Pampa biome indigenous plant that has desirable ornamental characteristics. To use a native plant in landscaping, a production protocol is required. It is important to compare production techniques and their performance with a rustic flower bed species as Verbena hybrida and it is also important to evaluate the effects of rock powder at the first six months of soil incubation. In this original study for the species, it's aimed to create a production protocol for the Peruvian Verbena through Five experiments: 1st) study of sexual propagation of the species through the diagnosis of photoblastic characteristic and need to scarification of seeds. The results show that the seed have positive photoblastic trait and scarification by pinching is not indicated. Seed germination was low and propagation by cuttings is most appropriate. The second and third experimento describe the asexual propagation: 2nd) dealt with the assessment of cuttings development and the need of synthetic auxin on rooting induction, in which the cuttings had good root formation after 21 days post-cutting proceed and lack of response to use of artificial auxin; 3rd) performed with a commercial species (Verbena hybrida) from Verbenaceae family, the aim of the experiment is to evaluate the effects of different substrates and of the use of rock dust at cutting process of Verbenaceae plant. The use of rock dust did not show efficiency because of its slow release of nutrients. The use of rock powder at Verbenaceae cultivation was also tested in the fourt h experiment: 4º) conducted at field for the evaluation of rock dust effects at soil active and potential acidity, SMP índex, Ca2+, Mg2+ K, Al3+, P levels and content of soil organic matter in flower bed soil under ornamental cultivation. The study showed that the application of 1 t.ha-1of rock dust was insufficient to provide soil nutrients in six months. However, the use of rock dust is recommended for long -term nutrition for plants in bed cultivation. The fifth experiment was also conducted on flower bed: 5th) evaluated the ornamental and landscaping potential and plasticity of Peruvian Verbena, comparing the species with V. hybrida and assessing the rock dust effects in the plants. Growth parameter were analysed at 34 and 120 days after planting. Between the species, number of flowers per inflorescence and flower diameter were also compared. There was no effect of using rock powder in plants development, which showed similar growtn parameters. The results confirn the Peruvian Verbena aptitude to be used as ornamental plant for flower bed and flower borders in landscaping. The number of flowers per inflorescence did not iffer between the species, V. hybrida flower are larger, bur the Peruvian Verbena stands out for the colos of flowers. The unquestionable beauty and hardiness common to native species make the Peruvian Verbena na excellent opition for use in landscaping projects for public, low maintenance and degraded areas.